Efektivitas Program Penanaman Pohon untuk Lingkungan Keberlanjutan dalam Melawan Perubahan Iklim - Milawati Valantia; Novia Safitri; M. Rizki; Alfi Hidayat; Nindi Ayu Lestari; Try Adhi Bangsawan; Santi Santi (Lembaga Pengembangan Kinerja Dosen, 2024)
Tree planting as a reforestation strategy is an important solution to overcome environmental and social problems in villages. This journal discusses the effectiveness of the tree planting program implemented in Mekar Agung Village, using an environmental and social approach. The program aims to improve environmental quality, reduce the impact of climate change, and strengthen social solidarity in village communities. The methodology used includes the implementation of planting activities, impact evaluation through measurement of environmental parameters such as reducing soil erosion and improving air quality, as well as analyzing changes in attitudes and community involvement. The results show that the program is effective in improving environmental quality, with significant improvements in soil and air quality. In addition, this program has also succeeded in strengthening social relations between residents through active participation in reforestation activities. These findings underscore the importance of an integrated approach that combines environmental and social aspects in greening programs to achieve sustainable and significant results.